3D chaos lidar system with a pulsed master oscillator power amplifier scheme - Chen, Jun-Da; Ho, Hsin-Lin; Tsay, Han-Ling; Lee, You-Lin; Yang, Ching-An; Wu, Kuan-Wei; Sun, Jia-Long; Tsai, Da-Jie; Lin, Fan-Yi (Optics express, 2021)
We investigated the characteristics of chaos-modulated pulses amplified by a pulsed master oscillator power amplifier (MOPA) for application in a new chaos lidar system in this study. Compared with the loss modulation applied in a continuous-wave (CW) time-gating scheme, the pulsed MOPA scheme could generate chaos-modulated pulses with much higher peak power, resulting in an improved peak-to-standard deviation of sidelobe level (PSL std ) in correlation-based lidar detection. When the pulsed MOPA scheme was applied at a duty cycle of 0.1% and pulse repetition frequency of 20 kHz, which correspond to specifications compliant with eye safety regulations, it outperformed the CW time-gating scheme with respect to PSL std by 15 dB. For the first time, we applied the chaos lidar system with the pulsed MOPA scheme to execute high-resolution, high-precision three-dimensional (3D) face profiling from a distance of 5 m. We also added the corresponding PSL std value to each pixel in the point clouds to generate false-color images; thus, we obtained 3D images of a scene with multiple objects at a range of up to 20 m.